Development of oil, freeze, high temperature resistant and flame retardant rubber compounds for high performance hydrolic hose - Kemal Karadeniz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The highperformance hydrolic rubber hose should resist to hydrolic oils and can run attemperature interval from –55 0C to 150 0C. In additionto these properties, for some areas such as mining should also be flameretardant. In this study, compound formulations having properties mentionedabove were developped, mechanical properties, hydrolic oil and low, hightemperature resistance performances were measured. Flame retardant tests werealso been performed. Hoses were built using these newely developped compoundsand then their burst tests were performed. The best performer compound for lowtemeperature performance hose was the one prepared with the blends of acrylonitrilebutadiene (NBR), stirene-butadiene (SBR)and cis-butadiene (CBR) rubbers along with plasticizer diisononylphthalate (DINP).One of the compounds preapared with the blending of SBR, NBR rubbers, aluminiumhydroxide, tricrezyl phoshate (TCP) and zinc borate was the best for the flameretardant hose. The best performer high temeperature resistant compound waspreapred using MT N990 carbonblack and plasticizer paraplex G50 with blendingof SBR 1502, NBR 2860 and NBR 3360 rubbers.